2013
DOI: 10.3390/medicina49070047
|View full text |Cite
|
Sign up to set email alerts
|

Mildronate and its Neuroregulatory Mechanisms: Targeting the Mitochondria, Neuroinflammation, and Protein Expression

Abstract: This review for the first time summarizes the data obtained in the neuropharmacological studies of mildronate, a drug previously known as a cardioprotective agent. In different animal models of neurotoxicity and neurodegenerative diseases, we demonstrated its neuroprotecting activity. By the use of immunohistochemical methods and Western blot analysis, as well as some selected behavioral tests, the new mechanisms of mildronate have been demonstrated: a regulatory effect on mitochondrial processes and on the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 81 publications
1
11
0
1
Order By: Relevance
“…Further studies demonstrated an increase in endurance performance of athletes, improved rehabilitation after exercise, protection against stress, and enhanced activations of central nervous system (CNS) functions . Moreover, Mildronate shows mood‐improving effects as well as an increased learning and memory performance, which are properties athletes may also benefit from . In dubious online shops, the performance‐enhancing effects of Mildronate are advertised overtly .…”
Section: Introductionsupporting
confidence: 91%
“…Further studies demonstrated an increase in endurance performance of athletes, improved rehabilitation after exercise, protection against stress, and enhanced activations of central nervous system (CNS) functions . Moreover, Mildronate shows mood‐improving effects as well as an increased learning and memory performance, which are properties athletes may also benefit from . In dubious online shops, the performance‐enhancing effects of Mildronate are advertised overtly .…”
Section: Introductionsupporting
confidence: 91%
“…One concept of the neurological actions of meldonium is that due to its structural similarity to L-carnitine, it could act as a carnitine-mimicking substance (‘false carnitine’28). High concentrations of meldonium should lead to a negative feedback, with the consequence of a compensatory decrease in intracellular L-carnitine.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of meldonium should lead to a negative feedback, with the consequence of a compensatory decrease in intracellular L-carnitine. Therefore, meldonium was suggested to fulfil the criteria as a replacement medication for L-carnitine 28. In different animal models of neurotoxicity and neurodegenerative diseases, meldonium was shown to exhibit beneficial effects in the regulation of neuroinflammation, neuroregeneration and apoptosis, with its main actions on the regulation of mitochondrial processes and the expression of nerve-cell proteins 28–32.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В ряде клинических наблюдений была показана высокая эффективность мельдония при острой церебральной ишемии, заключавшаяся в зна-чимом регрессе основных клинико-неврологических симптомов, улучшении когнитивных функций, норма-лизации биоэлектрической активности головного моз-га и показателей гемодинамики [4,7,14,20]. При этом эффективность данного препарата, по мнению исследо-вателей, напрямую связана с его воздействием на меха-низмы энергокоррекции [3,15,16]. Кроме того, за счет индуцирования эндотелиальной NO-синтазы, стиму-лирующей синтез NO, а также вазодилатации, мельдо-ний оказывает позитивное действие на гемодинамику ишемизированных зон головного мозга [8,9,12,18,20].…”
unclassified